Analisis Tren Topik Publikasi Ilmiah Dosen Jurusan Teknik Komputer Menggunakan Co-Words Analysis - Hamzah Syahbana Munthe; Riki Handoko (LPPM Universitas Putera Batam, 2023)
One important factor in the development of science is through research in the relevant field. This was done to answer various problems and expand the scope of knowledge in this field of science. In Indonesia, seminars are conducted by both government and non-government institutions with the aim of being a forum for academics, practitioners, and researchers to re-correct the results of scientific articles in order to perfect these scientific articles. Previous bibliometric researchers more often studied papers, theses, dissertations and scientific journals. This is done to view usage, collection, obsolescence of information, knowledge mapping, etc. Based on the information above, the following is the background of this research, first, there is no scientific mapping to see trends in research topics, especially in scientific articles in the field of computer science, especially in the Computer Engineering and informatics department. Based on the formulation of the problem to be studied related to research topic trends and bibliometric studies of scientific articles in the proceedings in the field of computer science and information at seminars and conferences in Indonesia, a measuring instrument in the form of numbers will be used. The results of this study indicate that the trend of article research topics that are developing in the 2021-2023 period are data science and IoT, while the results of the citation analysis carried out show that the most widely used type of literature in writing scientific articles is journal literature (93.49%).